Long-term evaluation of cardiac and vascular toxicity in patients with Philadelphia chromosome-positive leukemias treated with bosutinib - Cortes, Jorge E. (Am J Hematol, 2016)
Vascular and cardiac safety during tyrosine kinase inhibitor (TKI) therapy is an emerging issue. We evaluated vascular/cardiac toxicities associated with long-term bosutinib treatment for Philadelphia chromosome-positive (Ph+) leukemia based on treatment-emergent adverse events (TEAEs) and changes in QTc intervals and ejection fraction in two studies: a phase 1/2 study of second-/third-/fourth-line bosutinib for Ph+ leukemia resistant/intolerant to prior TKIs (N = 570) and a phase 3 study of first-line bosutinib (n = 248) versus imatinib (n = 251) in chronic phase chronic myeloid leukemia. Follow-up time was ≥48 months (both studies). Incidences of vascular/cardiac TEAEs in bosutinib-treated patients were 7%/10% overall with similar incidences observed with first-line bosutinib (5%/8%) and imatinib (4%/6%). Few patients had grade ≥3 vascular/cardiac events (4%/4%) and no individual TEAE occurred in >2% of bosutinib patients. Exposure-adjusted vascular/cardiac TEAE rates (patients with events/patient-year) were low for second-line or later bosutinib (0.037/0.050) and not significantly different between first-line bosutinib (0.015/0.024) and imatinib (0.011/0.017; P ≥ 0.267). Vascular/cardiac events were managed mainly with concomitant medications (39%/44%), bosutinib treatment interruptions (18%/21%), or dose reductions (4%/8%); discontinuations due to these events were rare (0.7%/1.0%). Based on logistic regression modelling, performance status >0 and history of vascular or cardiac disorders were prognostic of vascular/cardiac events in relapsed/refractory patients; hyperlipidemia/hypercholesterolemia and older age were prognostic of cardiac events. In newly diagnosed patients, older age was prognostic of vascular/cardiac events; history of diabetes was prognostic of vascular events. Incidences of vascular and cardiac events were low with bosutinib in the first-line and relapsed/refractory settings following long-term treatment in patients with Ph+ leukemia.